NILAI MORAL TRADISI BUKA LUWUR SEBAGAI MEDIA PENANAMAN PENDIDIKAN KARAKTER ANAK - Ghina Salsabila; Wawan Shokib Rondli; Rani Setiawaty - (STKIP Subang, 2024)
This research aims to describe the process of implementing the Buka Luwur Syekh Abdul Ghofur tradition in Bae Village, Bae District, Kudus Regency and identify the moral values ​​contained in it. This research uses the Qualitative Narrative Inquiry Method. Data collection techniques included observation, in-depth interviews, note-taking, and taking pictures, with data analysis using a qualitative narrative approach as the objects were the 5th grade children of SD Bae and local residents. The benefits of research are helping children to understand and appreciate the moral values ​​contained in the buka luwur tradition and can be an effective means for cultivating educational character. Research findings show that there are four moral values ​​in the Buka Luwur Tradition: caring for the environment through cleaning activities, religious values ​​through reciting the Koran and praying together, social care through salvation and providing assistance to orphans, as well as cooperation in installing luwur and other activities.